Distribution of Zakat Resources to Further Sustainable Development Goals Through The Mitigation of Poverty in Baznas, Republic of Indonesia - Haanii Haritsa Yuzen; Yerna Wiza; Karmila Sari; Aidil Alfin (ICIEFS Proceeding, 2024)
The eradication of poverty and inequality represents a contemporary challenge that the Sustainable Development Goals (SDGs) seek to address. The SDGs themselves are an extension of the prior framework established by the Millennium Development Goals (MDGs), which were formulated by the United Nations and endorsed by 193 nations. The SDGs are rooted in universal principles, integrity, and inclusivity to ensure that all stakeholders can participate without exception, encapsulated in the principle of "No One Left Behind." The SDGs encompass 17 objectives and 169 targets for achievement, with the expectation of realization by the year 2030. The contribution of zakat towards the advancement of the SDGs is further reinforced by Law No. 23 of 2011 regarding the Management of Zakat, which articulates that zakat functions as a religious institution aimed at enhancing justice and the welfare of the community. Moreover, Article 3 of the same legislation delineates the objectives of zakat management, which include: 1) Enhancing the effectiveness and efficiency of zakat management services, and 2) Augmenting the benefits of zakat to promote community welfare and alleviate poverty.